The protective effect of thymoquinone over olanzapine-induced side effects in liver, and metabolic side effects - Bilgic, S.; Korkmaz, Tastemir D.; Azirak, S.; Guvenc, A. N.; Kocaman, N.; Ozer, M. K. (Comenius Univ, 2017)
OBJECTIVES: The aim of the study was to investigate the possible protective qualities of thymoquinone (TQ) against the side-effects of olanzapine (OLZ) in an experimental model in rat liver with histologic and biochemical assessments. METHODS: Experimental procedures were performed on 35 female Sprague Dawley rats. Rats were randomly divided into five groups as: group 1: control; group 2: OLZ; group 3: OLZ+TQ-1; group 4: OLZ+TQ-2; and group 5: OLZ+TQ-3. RESULTS: The results showed that a 2-week administration of OLZ (4 mg/kg, once a day for the first week, 8 mg/kg once a day for the second week, p.o.) and treatment with TQ (25, 50, 100 mg/kg, once daily, p.o.) significantly reduced weight gain induced by OLZ. In addition, TQ increased the total antioxidant status (TAS), high-density lipoprotein cholesterol (HDL), insulin levels and decreased serum oxidative stress index (OSI), total oxidant status (TOS), alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma glutamyl transpeptidase (GGT), low density lipoprotein cholesterol (LDL), glucose, triglycerides (TG) and total cholesterol (CH) levels significantly (p < 0.05). CONCLUSION: This study revealed that treatment with TQ might protect liver tissue against the side-effects of OLZ. TQ could be an effective course of therapy to enhance therapeutic efficacy
Keywords: thymoquinone; olanzapine; adverse effects; liver; weight gain/loss; apoptosis